2023
DOI: 10.1039/d2nj05844h
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-assisted colorimetric determination of uranyl ions in aqueous solutions

Abstract: A convenient and portable smartphone-assisted method for the colorimetric detection of uranyl ions (UO22+) in aqueous solutions was proposed taking rifampicin and 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (Br-PADAP) as chromogenic agents. The addition of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…62 Lei et al reported on the determination of uranyl ions in aqueous solutions by a smartphone-assisted colorimetric method. 63 Photographs of samples taken with smartphones can be processed instantly with smartphone applications, and accurate data such as RGB (red, green, blue), 64,65 CMYK (cyan, magenta, yellow, black) values 66 and other detailed data can be obtained. 67 Since the colour change of a sample shows a linear relationship with the substance content, the corresponding concentration can be determined from the colour data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Lei et al reported on the determination of uranyl ions in aqueous solutions by a smartphone-assisted colorimetric method. 63 Photographs of samples taken with smartphones can be processed instantly with smartphone applications, and accurate data such as RGB (red, green, blue), 64,65 CMYK (cyan, magenta, yellow, black) values 66 and other detailed data can be obtained. 67 Since the colour change of a sample shows a linear relationship with the substance content, the corresponding concentration can be determined from the colour data.…”
Section: Introductionmentioning
confidence: 99%
“…63 Photographs of samples taken with smartphones can be processed instantly with smartphone applications, and accurate data such as RGB (red, green, blue), 64,65 CMYK (cyan, magenta, yellow, black) values 66 and other detailed data can be obtained. 67 Since the colour change of a sample shows a linear relationship with the substance content, the corresponding concentration can be determined from the colour data. 68,69 Compared to simply observing colorimetric results with the naked eye, more accurate results can be obtained by using a smartphone.…”
Section: Introductionmentioning
confidence: 99%